Rethinking modernity and national identity in Turkey - Kasaba, Resat; Bozdoğan, Sibel (Seattle : University of Washington Press, 1997)
Kemalist certainties and modern ambiguities /; Resat Kasaba --; Whither the project of modernity? Turkey in the 1990s /; Çaglar Keyder --; Modernization policies and Islamist politics in Turkey /; Haldun Gülalp --; Projects as methodology : some thoughts
Keywords: Social change -- Turkey; Toplumsal değişim -- Türkiye; Nationalism -- Turkey; Milliyetçilik -- Türkiye; Turkey -- Civilization -- 20th century; Türkiye -- Uygarlık -- 20. yüzyıl